ADAR1-dependent editing regulates human β cell transcriptome diversity during inflammation - Szymczak, Florian; Cohen-Fultheim, Roni; Thomaidou, Sofia; de Brachène, Alexandra Coomans; Castela, Angela; Colli, Maikel; Marchetti, Piero; Levanon, Erez; Eizirik, Decio; Zaldumbide, Arnaud (Frontiers in Endocrinology, 2022)
Introduction Enterovirus infection has long been suspected as a possible trigger for type 1 diabetes. Upon infection, viral double-stranded RNA (dsRNA) is recognized by membrane and cytosolic sensors that orchestrate type I interferon signaling and the recruitment of innate immune cells to the pancreatic islets. In this context, adenosine deaminase acting on RNA 1 (ADAR1) editing plays an important role in dampening the immune response by inducing adenosine mispairing, destabilizing the RNA duplexes and thus preventing excessive immune activation. Methods Using high-throughput RNA sequencing data from human islets and EndoC-βH1 cells exposed to IFNα or IFNγ/IL1β, we evaluated the role of ADAR1 in human pancreatic β cells and determined the impact of the type 1 diabetes pathophysiological environment on ADAR1-dependent RNA editing. Results We show that both IFNα and IFNγ/IL1β stimulation promote ADAR1 expression and increase the A-to-I RNA editing of Alu-Containing mRNAs in EndoC-βH1 cells as well as in primary human islets. Discussion We demonstrate that ADAR1 overexpression inhibits type I interferon response signaling, while ADAR1 silencing potentiates IFNα effects. In addition, ADAR1 overexpression triggers the generation of alternatively spliced mRNAs, highlighting a novel role for ADAR1 as a regulator of the β cell transcriptome under inflammatory conditions.